General Geology With Emphasis On Structural Geology Of The Chert Member Of Semanggol Formation, Kebun 500, Pokok Sena, Kedah - Ahmad, Muhammad Hafiz (2016)
The study is being conducted at the Kebun 500 area which includes an undulated terrain consisting of hills and ridges of upper and lower Paleozoic rocks that has been mapped as the Semanggol Formation and the Mahang Formation. Comprehensive geological study which includes type of rock, physical properties of the rocks, lineation and planar measurement of the study area were recorded in order to reconstruct the deformational histories of the study area. The presence of black coloured rock at the outcrop also make the study interesting because the main type of rock for the outcrop at the study area is chert interbedded with mudstone which is reddish brown and pale grey in colour due to weathering. Total carbon analysis will be carried out to determine the type of the black coloured rock in relation with the depositional environment of the study area. The reference point is established at the area with different cyclic event. Thin section analysis are conducted to identify type of mineral in rock which is useful in revealing the evolution of the parent rock. The study has demonstrated that the strike of Kebun 500 area is generally in N-S trending direction and the force of compression comes from East – West direction. The westward thrusting of Sibumasu Terrane is believed to provide abundant chert which probably originates from the bed of Palaeo-Tethys Ocean. There is unique secondary geologic structures at the study area which is fold. Fold are bend in the earth crust and can be identified by the change in the direction of dip of rock units. Sedimentary way-up structure that can be observed in the study area is graded bedding at the third cyclic event. It is anticipated that this project will provide information in the structural geology of the study area and explain the relationship between the outcrop at the study area with Semanggol Formation.